PERAN SERANGGA AKUATIK SEBAGAI BIOINDIKATOR PENCEMARAN LINGKUNGAN PERAIRAN: A SYSTEMATIC LITERATURE REVIEW - Ananda Siddiq Lubis; Dea Puspita; Putri Indah Sari; Jalilah Azizah Lubis (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2026)
This study aims to analyze the role of aquatic insects as bioindicators in assessing water pollution levels and aquatic environmental quality using a Systematic Literature Review (SLR) approach. The method follows the PRISMA guidelines, including identification, screening, eligibility, and inclusion stages of scientific articles obtained through a structured search query. Based on predefined inclusion and exclusion criteria, a total of 10 empirical research articles published between 2020 and 2026 were selected. The synthesis results indicate that Ephemeroptera, Plecoptera, and Trichoptera (EPT) groups are highly sensitive to pollution and represent good water quality conditions, whereas Diptera and Hemiptera are more tolerant of polluted environments. Environmental parameters such as dissolved oxygen (DO), pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), and total suspended solids (TSS) significantly influence aquatic insect community structure. This study contributes to the advancement of environmental education and aquatic ecology by reinforcing biomonitoring approaches as a more integrative method for water quality assessment compared to conventional physicochemical analyses.